2009
DOI: 10.1021/jp9090393
|View full text |Cite
|
Sign up to set email alerts
|

Controllable and Large-Scale Synthesis of Carbon Nanofibers, Bamboo-Like Nanotubes, and Chains of Nanospheres over Fe/SnO2 and Their Microwave-Absorption Properties

Abstract: Carbon nanofibers (CNFs), bamboo-like carbon nanotubes (CNTs), and chains of carbon nanospheres (CNSs) were produced selectively in large quantities in the pyrolysis of acetylene at 500, 600, and 700 °C, respectively, over Fe/SnO2 nanoparticles generated by means of a combined sol−gel and hydrogen-reduction method. One advantage of this approach is that there is no need of using a dilute gas such as argon or nitrogen. It is found that the pyrolysis temperature has considerable effect on the yield, morphology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…Firstly, the multi-interfaces and triple junctions (graphene@Fe 3 O 4 , Fe 3 O 4 @SiO 2 , SiO 2 @PANI) are advantageous for electromagnetic attenuation due to the existing interfacial polarization [22]. Secondly, the PANI and the void space existing between Fe 3 O 4 and PANI result in relatively large specific surfaces areas, providing more active sites for reflection and scattering of electromagnetic wave [23]. Finally, the void space between Fe 3 O 4 and PANI can effectively interrupt the spread of electromagnetic wave and generate dissipation due to the existing impendence difference and enhanced the microwave absorption properties [24].…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the multi-interfaces and triple junctions (graphene@Fe 3 O 4 , Fe 3 O 4 @SiO 2 , SiO 2 @PANI) are advantageous for electromagnetic attenuation due to the existing interfacial polarization [22]. Secondly, the PANI and the void space existing between Fe 3 O 4 and PANI result in relatively large specific surfaces areas, providing more active sites for reflection and scattering of electromagnetic wave [23]. Finally, the void space between Fe 3 O 4 and PANI can effectively interrupt the spread of electromagnetic wave and generate dissipation due to the existing impendence difference and enhanced the microwave absorption properties [24].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was found that, when using acetylene decomposition over Fe nanoparticles to synthesize CNTs, the addition of different amounts of H2 led to the formation of CNTs with various helicities [46]. Afterwards, the same authors synthesized Fe/SnO2 nanoparticles by using a combined sol-gel/reduction method and then used this catalyst in the pyrolysis of acetylene for selective synthesis of carbon nanofibers (CNFs), bamboo-like carbon nanotubes (CNTs), and chains of carbon nanospheres (CNSs) [47]. They found that the pyrolysis temperature, 500, 600, or 700 °C, had a considerable effect on the yield, morphology, and microwave absorption properties of the obtained materials.…”
Section: Hydrocarbon Thermal Decompositionmentioning
confidence: 99%
“…or CO feedstocks and various metal particle catalysts such as Fe, Ni, or Co have been used for the growth of MWCNT on different substrates by CVD. Typical bamboo-like CNFs obtained from the Ni 47 Cu 53 /CNT catalyst at 750 • C are shown in Figure 6.…”
Section: Special Chemical Vapor Depositionmentioning
confidence: 99%
“…Qi et al reported the microwave absorbing property of bamboo-like carbon nanotubes over Fe/SnO 2 composite and the minimum reflection loss was À11.06 dB at 12.45 GHz [13]. A composite of epoxy-silicone filled with multi-walled carbon nanotubes (MWCNTs) and carbonyl iron particles was used as microwave absorber and showed a minimum reflection loss of À16.9 dB at 10.5 GHz.…”
Section: Introductionmentioning
confidence: 99%